Analysis of Cash Receipts Accounting Information Systems in Improving The Internal Control System PT. Cipt Niaga Semesta Pelabuan Ratu - Gunawan, Debi; Sofiani, Venita; Himawan, Irfan Sophan (Journal of Management, Economic, and Accounting, 2023)
Every product sales transaction has something called cash receipts for the company. Company management must be able to manage every transaction to avoid fraud or mistakes that can be intentional or unintentional. The type of research used by the author is descriptive qualitative method, the data processed is data obtained from interviews and unstructured observations which will be analyzed qualitatively and described in descriptive form. The accounting information system for cash receipts at PT Cipta Niaga Semesta Pelabuhan Ratu has been satisfactory in improving the company's internal control. However, companies need to pay attention to internal controls related to the structure that separates the performance of duties and functions of employees, as well as adding human resources in several parts to avoid a decrease in employee performance which can harm the company.